The Impact of Electronic Cigarettes on Male Fertility : A Literature Review - Vianita Rizky Ardiantari; Fikri Rizaldi (Universitas Airlangga, 2025)
The use of e-cigarettes has become a trend in populations recently, even though the effects caused by e-cigarettes are not much different from traditional cigarettes. Male infertility caused by stressful social factors and addictive disorder such as alcoholism, drug addiction, and smoking also has been increased. E-cigarettes lead to increased sympathetic activation and oxidative stress it can cause significant damage to endothelial cells. Nicotine exposure acutely raises sympathetic nervous system activity, causing vasoconstriction through the release of norepinephrine and epinephrine, which reduces penile blood flow. The well-known equation endothelial dysfunction equals erectile dysfunction clearly illustrates how ischemia and hypoxia lead to endothelial dysfunction and increased collagen synthesis, resulting in vasculogenic ED. some of the additives used in e-cigarettes could affect spermatogenesis.